Perlindungan Hukum Terhadap Online Shop Yang Melakukan Promosi (Endorsement) Pada Selebgram Di Kota Mataram - Indah Permata Sari; Diangsa Wagian (Private Law, 2022)
This study aims to determine how Selebgram will provide legal relationship and legal protection toward the online shop in the endorsement agreement in the event of a default. This research uses the empirical normative legal method. Based on the research results, the legal relationship between endorsement agreements made by celebgram in Mataram with online shops is a form of certain service agreements, which are one type of work agreement regulated in the Civil Code (KUHPerdata) article 1601 and article 1617. The legal protections provided by the program on the online shop is compensation in the form of refunds and goods based on preventive and repressive legal protection, and the form of compensation is regulated in Article 19 of the Consumer Protection Lawthat regulated responsibilities of business actors/endorsement service providers.